Facile synthesis of efficient heterogeneous photocatalytic and highly dielectric Bi4BaTi4O15 ceramic with remarkable applicability in the degradation of rhodamine B dye - Singh S.; Kumar A.; Pandey S.K.; Singh D.K.; Kumar V.; Verma M.K.; Gupta A.; Tiwary D.; Mandal K. (My University, 2025)
Bi4BaTi4O15(BBTO), an Aurivillius oxide, which is a mixed metal bismuth–layered based oxide fabricated by chemical route, has shown highly efficient photocatalytic activity in degradation of organic dye besides possessing high dielectric constant. The obtained material was characterised by various techniques like Fourier Transform Infrared (FTIR), transmission electron microscope, Scanning Electron Microscopy-Energy Dispersive X-rays Spectroscopy (SEM-EDX) X-ray powder diffraction (XRD), Zetasizer Nano-ZS, Ultraviolet- differential reflectance spectroscopy (UV-DRS), Brunauer–Emmett–Teller, Atomic Force Microscopy (AFM) and X-ray photoelectron spectra for the phase identification, microstructural analysis, bandgap determination, elemental analysis and oxidation state of the material. XRD data confirm the presence of single-phase BBTO ceramic, corroborated by Le-Bail fitting analysis. A high dielectric constant value of 3.08 × 103 was obtained for the BBTO ceramic at 368 K. The material is stable in suspension form in solution and is a highly efficient photocatalyst. BBTO degraded 80% of RhB dye within 1 h of time period under UV light via major reactive species OH . radicals and O2.-, generated during the photocatalytic reaction, which is proved to be following the first-order kinetics. © 2021 Informa UK Limited, trading as Taylor & Francis Group.